2016
DOI: 10.1111/jfs.12289
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation and Antibacterial Activity of Enterococci Isolated from Lighvan Cheese

Abstract: Twenty three enterococci were isolated from Lighvan cheese. Enterococcal isolates identified by 16S rDNA sequencing, were evaluated for their safety and also examined for antibacterial activity and presence of the genes coding for enterocins. Four enterococcal isolates exhibited inhibitory activity against Listeria innocua and E. faecalis and harbored the bacteriocin genes (enterocins A, B, P, X and 31) too. Multiple combinations of virulence determinant genes (vanA, vanB, gelE, esp, asa1, cpd and ace) were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
3
1
Order By: Relevance
“…As a result of PCR analysis, three PCR bands were detected in E. faecium BT29.11 strain: 126 bp with entA (Figure 4, line 1), 162 bp with entB (Figure 4, line 2) as expected, and 450 bp with entX (Figure 4, line 5), instead of the expected 500 bp. The presence of entA, entB, and entX has been found together in E. faecium strains isolated from Turkish Tulum and Beyaz cheeses (Avcı and Özden Tuncer, 2017), Lingvan cheese (Joghataei et al, 2017), and boza (Gök Charyyev et al, 2019), as confirmed in this study. These data suggest that strain BT29.11 might express more than one enterocin.…”
Section: Detection Of Enterocin Genes In E Faecium Bt2911supporting
confidence: 86%
“…As a result of PCR analysis, three PCR bands were detected in E. faecium BT29.11 strain: 126 bp with entA (Figure 4, line 1), 162 bp with entB (Figure 4, line 2) as expected, and 450 bp with entX (Figure 4, line 5), instead of the expected 500 bp. The presence of entA, entB, and entX has been found together in E. faecium strains isolated from Turkish Tulum and Beyaz cheeses (Avcı and Özden Tuncer, 2017), Lingvan cheese (Joghataei et al, 2017), and boza (Gök Charyyev et al, 2019), as confirmed in this study. These data suggest that strain BT29.11 might express more than one enterocin.…”
Section: Detection Of Enterocin Genes In E Faecium Bt2911supporting
confidence: 86%
“…In the study of Joghatei et al, resistance to erythromycin, tetracycline and ciprofloxacin was 40%, 20% and 8% respectively. While in our study the resistance tetracycline, erythromycin, and norfloxacin was reported to 83.33%, 46.67% and 30% (35). Resistance to the antibiotics mentioned in our study is higher than that of Joghatei et al, Aminoglycosides are still valuable in the treatment of bacterial infections, despite their side effects and problems associated with increased resistance of microorganisms to these drugs.…”
Section: Discussioncontrasting
confidence: 56%
“…The protein of the aggregate that carries the asa1 gene in enterococci is produced in response to sex pheromones that cause these bacteria to be absorbed into each other and form a cell mass. It also plays an important role in stimulating adhesion, invading cells and destroying myocardial and lung tissues (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Enterococci members were the predominant LAB, and correlation analyses revealed a positive link between Enterococci and amino nitrogen, suggesting that enterococcus may contribute to proteolysis in the pre‐fermentation of BS. Despite some authors considering that enterococcus may have virulence genes, related to common human pathogens, many researchers have found that enterococci exist widely in fermented foods, which are contributing factors to flavor formation and bioprotection.…”
Section: Discussionmentioning
confidence: 72%